Sistem Ujian Online Essay Kolektif Berbasis Gambar Studi Kasus Kampus PTKI Medan - Abdul Azis Rahmansyah; Poltak Evencus Hutajulu (STMIK Budi Darma, 2021)
The Covid-19 pandemic is a disaster for all of us, Vocational Education is also affected by the Covid-19 pandemic which forces online lectures, one of which is at the Industrial Chemical Technology Polytechnic (PTKI), in the implementation of the exam at PTKI Medan carried out collectively with questions exam in the form of an essay. There have been many studies on online essay exams but the scope of the discussion is for automatic correction or similarity based on text input. In vocational education, especially PTKI Medan, which has a test that is not limited to text input but there are calculations. Another weakness of text input is that the answers can be more easily copied and pasted by students. This research was carried out for 1 year starting from Odd semester 2020 to Even 2020. The method in developing information systems uses the waterfall model with the stages of needs analysis, system design, coding, implementation and the last stage of system maintenance. From the results of the research in the odd semester of 2020, the researchers used a text-based online essay exam model, but many weaknesses were found, one of which was the ease of students in using answers from the internet which were directly entered into the answer column. At the maintenance stage, the researcher updates the system by changing the image-based exam model, so students must write their answers on paper and then upload the answers to the website. The file upload system can overload the server if it is not controlled, one of the techniques used is to compress image files uploaded by students to the system and the maximum size can be compressed up to 78.48% from 1329 Kb to 286 Kb for this type. png data. In addition, to make it easier for lecturers to check answers, use the ezoom.js feature as a means to view answers in the form of images that are useful for zooming in, zooming out, rotating the answer images. Ezoom.js is a javascript that can be installed on php-based websites